Hubungan Faktor Maternal dengan Status Gizi Anak Usia 6-23 Bulan di Wilayah Kerja Puskesmas Ingin Jaya Kabupaten Aceh Besar - Usrina, Nora; Norisa, Nanda; Zahara, Evi; Raisah, Putri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Cases of malnutrition are currently still a serious problem in Indonesia, where they often occur in children under five years of age. If malnutrition is not addressed, it will have negative impacts on children under five. The impacts that occur include death and chronic infections. The nutritional status of children under five is influenced by socio-economic conditions, including maternal education, maternal occupation, number of children, knowledge and overall economic conditions of parents. To determine the relationship between maternal factors and the nutritional status of children aged 6-23 months in the working area of the Want Jaya Community Health Center, Aceh Besar Regency. This research uses a quantitative type of research with a cross sectional approach. The subjects in this research were mothers who had toddlers aged 6-23 months who were in the working area of the Want Jaya Community Health Center, Aceh Besar Regency. This research will be carried out for 6 months starting in April - September 2023. The research location will be carried out in the working area of the Want Jaya Community Health Center, Aceh Besar Regency. The instrument used in this research was a questionnaire, each variable containing 15 - 25 statement items. Data were analyzed using the chi-square test with a p value ≥ 0.05. There is a significant relationship between the mother's education level and the nutritional status of children aged 6-23 months (p<0.05). There is no significant relationship between monthly family income, mother's employment, mother's knowledge of parenting styles, and number of children in the family with the nutritional status of children aged 6-23 months (p>0.05). There is a relationship between maternal education level and the nutritional status of children aged 6-23 months. There is no relationship between monthly family income, mother's employment, mother's knowledge of parenting styles, and number of children in the family with the nutritional status of children aged 6-23 months. Keywords: Maternal Factors, Malnutrition, Toddlers  ABSTRAK Kasus gizi buruk saat ini masih menjadi permasalahan serius di Indonesia dimana seringkali terjadi pada kelompok anak usia di bawah lima tahun. Kejadian gizi buruk apabila tidak diatasi akan menyebabkan dampak yang buruk bagi balita. Dampak yang terjadi antara lain kematian dan infeksi kronis. Status gizi anak balita salah satunya dipengaruhi oleh faktor kondisi sosial ekonomi, antara lain pendidikan ibu, pekerjaan ibu, jumlah anak, pengetahuan serta kondisi ekonomi orang tua secara keseluruhan. Untuk mengetahui hubungan faktor maternal dengan status gizi anak usia 6-23 bulan di wilayah kerja Puskesmas Ingin Jaya Kabupaten Aceh Besar. Penelitian ini menggunakan jenis penelitian kuantitatif dengan pendekatan cross sectional. Subjek dalam penelitian ini yaitu ibu yang mempunyai balita berusia 6-23 bulan yang berada di wilayah kerja Puskesmas Ingin Jaya Kabupaten Aceh Besar. Penelitian ini akan dilaksanakan selama 6 bulan dimulai pada bulan April - September 2023. Lokasi penelitian dilaksanakan di wilayah kerja Puskesmas Ingin Jaya Kabupaten Aceh Besar. Instrumen yang digunakan pada penelitian ini adalah satu buah kuisioner, masing-masing variabel berisi 15 – 25 item pernyataan. Data dianalisis menggunakan uji chi-square dengan nilai p ≥ 0.05. Ada hubungan secara signifikan antara tingkat pendidikan ibu dengan status gizi anak usia 6-23 bulan (p<0.05). Tidak ada hubungan secara signifikan antara pendapatan keluarga per bulan, pekerjaan ibu, pengetahuan pola asuh ibu, dan jumlah anak dalam keluarga dengan status gizi anak usia 6-23 bulan (p>0.05). Ada hubungan tingkat pendidikan ibu dengan status gizi anak usia 6-23 bulan. Tidak ada hubungan antara pendapatan keluarga per bulan, pekerjaan ibu, pengetahuan pola asuh ibu, dan jumlah anak dalam keluarga dengan status gizi anak usia 6-23 bulan. Kata Kunci: Faktor Maternal, Gizi Buruk, Balita